Fatores de risco da incidência de cárie dentária em crianças prematuras: um estudo de coorte prospectivo - Natália Moreira Teixeira (2020)
The aim of this prospective cohort study was to evaluate the incidence of dental caries lesions in a group of children born preterm and / or low birth weight (LBW). Children were assessed at baseline (T1) and after two years (T2) for risk factors for dental caries lesions, socioeconomic indicators and dietary habits. This study included a convenience sample of 42 premature and / or LBW children aged between 2 and 5 years-old, referred to the University Hospital of the Federal University of Minas Gerais (UFMG), Belo Horizonte, Brazil. The study was approved by the Human Research Ethics Committee of UFMG. Mothers who agreed to participate, signed the informed consent form. Two examiners diagnosed dental caries lesions using the criteria of the World Organization (WHO): cavitated, indicated extraction and filled teeth (dmft). Children were first examined in 2017 at the university hospital. Children are periodically scheduled for medical appointments at the hospital after the first year of life. Data collection was performed on the same day of the medical appointment. After the mothers completed the questionnaire, the children were examined for the diagnosis of dental caries lesions. Medical records were also evaluated to collect data on medical condition, gestational age and birth weight. After two years, the children were examined for a diagnosis of dental caries lesions. In cases where the children were not scheduled for medical appointments at the hospital, they were scheduled for dental examination at the Dental School of UFMG or visited at home. The data were tabulated in the SPSS software for descriptive statistical analysis, unadjusted and adjusted binomial model. Descriptive analysis was performed for the dependent variable incidence of dental caries lesions after two years. Negative binomial regression models were used to estimate the adjusted and unadjusted rate ratios (RR) and 95% confidence interval (CI) for confounding factors and incidence of dental caries lesions. After two years, 36 children (85%) were examined, aged between 4 to 7 years-old. The incidence of dental caries lesions was 36.7%. The adjusted negative binomial model showed that children born weighting between 1,000 to 1,500 g (RR: 0.23; 95% 0.08-0.72) and children born weighting between 1,500-2,500 g (RR: 0.06; 95% CI 0.01 -0.55) had less incidence of dental caries lesions compared to children born with less than 1,000 g. Children from families with lower income (R = 6.05; 1.05-34.84) had a higher ratio of dental caries lesions and children who did not consume sugared juice, tea or yogurt (RR = 0.21; 95% CI 0.07 -0.62) had a lower ratio of dental caries lesions. There was an inverse dose-response relationship between incidence of dental caries lesions and birth weight. Lower income and consumption of juice, tea or yogurt were risk factors for dental caries lesions.